Fluorescence assay for the determination of glutathione based on a ring-fused 2-pyridone derivative in dietary supplements. Issue 6 (22nd January 2021) - Kasprzyk, Wiktor; Koper, Filip; Flis, Agata; Szreder, Dominika; Pamuła, Elżbieta; Bogdał, Dariusz; Wybraniec, Sławomir; Ortyl, Joanna; Świergosz, Tomasz
Abstract : Herein, a novel fluorescent method for the determination of GSH levels in aqueous solutions involving the utilization of citric acid as a derivatization reagent was developed. Abstract : Herein, a novel fluorescent method for the determination of GSH levels in aqueous solutions involving the utilization of citric acid as a derivatization reagent was developed. Therefore, the crucial parameters of the derivatization process were established from what has resulted in the development of a sensitive, reproducible, and accurate GSH assay. The method was validated, and its applicability in the characterization of the GSH concentration in dietary supplements concerning the selectivity in the determination of GSH over GSSG was both confirmed. The chemical structure of the new fluorophore 3-[(carboxymethyl)carbamoyl]-5-oxo-2, 3-dihydro-5 H -[1, 3]thiazolo[3, 2- a ]pyridine-7-carboxylic acid – CTPC was elucidated using detailed NMR: one-dimensional ( 1 H, 13 C), as well as two-dimensional NMR spectra ( 1 H– 1 H COSY, 1 H– 13 C HSQC, 1 H– 13 C HMBC, 1 H– 15 N HSQC, 1 H– 15 N HMBC) experiments. Besides, the essential optical, biological and antioxidative properties of CTPC were investigated.